Estudio del sistema de producción de bañeras de volteo, en el taller de metalmecánica “Luis Iza”, para el mejoramiento de sus procesos, ubicado en la parroquia Eloy Alfaro, barrio San Felipe, durante el periodo 2014-2015 - Tandalla Chicaiza, José Wilfrido (2015)
This research was conducted at mechanical workshops "Luis Iza", dedicated to the manufacture of haul bed, it is located in Latacunga city , Cotopaxi Province, the study production of haul bed to improve their processes applied and resources invested by simplifying unnecessary activities for determining a suitable production time. It also emphasizes the need to apply flowcharts of processes, operations and lines the objectives in order to enhance the productive activities of the mechanical workshop by removing unnecessary tasks and improving others....